Effect of timed exercise interventions on patient-reported outcome measures: A systematic review - Mirey Karavetian; Cosette Fakih El Khoury; Femke Rutters; Romy Slebe; Diane Lorenzetti; Denis Blondin; André Carpentier; Jean-Pierre Després; Joris Hoeks; Andries Kalsbeek; Renée de Mutsert; Marie Pigeyre; et al. (PLoS ONE, 2025)
Background Exercising at a specific time of day has the potential to mitigate the negative effects of disrupted circadian rhythms caused by irregular work and sleep schedules on the development of chronic diseases. Afternoon/evening exercise is postulated to be superior to morning exercise for various health outcomes, but patient acceptance of timed exercise remains unclear. The aim of this systematic review was to assess the impact of exercise timing on patient-reported outcomes (PROMs). Methods We conducted a systematic review, following Cochrane and PRISMA guidelines (PROSPERO: CRD42022322646). We systematically searched databases including MEDLINE, SCOPUS, Embase, APA PsycInfo, CINAHL, and Web of Science, to identify studies which reported on PROMs related to timed exercise interventions: either acutely after a bout of exercise or following extended training (>1 month). Studies were included if they reported primary data from randomized or non-randomized experiments of timed exercise interventions (against any comparator), published in English until August 2023 and reporting on any PROM. Machine-learning software (AR Reviews) was used to aid in abstract screening. Subsequently, two independent reviewers reviewed the included full texts, extracted study details (participants, interventions, outcomes), and evaluated the risk of bias using Cochrane tools (ROB-2 and ROBINS-I). Exercise interventions were summarized using the TIDieR reporting method and results were presented in accordance with the Synthesis Without Meta-analysis (SWiM) guidelines for systematic reviews. Results Seventeen studies with 403 participants were included in the review. The interventions varied widely in exercise modality, duration, and participant characteristics, contributing to substantial heterogeneity in the findings. Most studies found no significant impact of exercise timing on PROMs. There was some inconsistency between studies for certain outcomes. Discussion The review suggests that there are no clear detrimental effects of afternoon or evening exercise on PROMs compared to morning exercise. However, the lack of homogeneity in study populations and small sample sizes resulting in low power for PROM outcomes are major limitations of the research in this field. If future research confirms the metabolic advantages of afternoon/evening exercise, this may be an acceptable alternative for individuals.